Effect of dietary taurine supplementation on growth, digestive enzyme, immunity and resistant to dry stress of rice field eel (Monopterus albus) fed low fish meal diets. (25th March 2018) - Hu, Yi; Yang, Gang; Li, Zhaolin; Hu, Yajun; Zhong, Lei; Zhou, Qiubai; Peng, Mo
Abstract: This study was conducted to evaluate the effect of dietary taurine supplementation on growth, immunity and resistant to dry stress of rice field eel ( Monopterus albus ) fed low fish meal diets. Six isonitrogenous and isolipid diets (32% fish meal) supplemented with six taurine concentrations (0, 0.3, 0.6, 0.9, 1.2 and 1.5 g/kg; designated as T0, T0.03, T0.06, T0.09, T0.12 and T0.15 groups, respectively) were prepared. A diet including 42% fish meal (FM group) was also included as a reference. The results showed that specific growth rate (SGR) in FM group was significantly higher than that in lower fish meal treatments. SGR significantly increased and slowly decreased with the increase in taurine supplementation level. Lipase activity value in intestine of M. albus fed FM diet was maximum, and with the increase in taurine supplementation level, lipase activity significantly increased and slowly decreased. The FM group had relative higher total antioxidant capacity (T‐AOC) content, catalase (CAT), total superoxide dismutase (T‐SOD), and lyzozyme (LZM) activities in serum than the other groups. With the increase in dietary taurine supplementation level, the CAT, T‐SOD, T‐AOC and LZM activities in serum significantly increased and then decreased. In the dry stress experience, the adrenaline (AD), cortisol (COR), glucose (GLU), total cholesterol (CHOL), and malondialdehyde (MDA) concentrations, T‐AOC content, CAT and T‐SOD activities in serum of M. albus in the four groups first increased and reached the peak at 2 hr, and then decreased under air‐exposure stress. Compared to the FM group, T0.15  group had relative higher T‐AOC content, CAT and T‐SOD activities, and lower AD, COR GLU, TC and MDA concentrations.